2022
DOI: 10.3390/molecules27133984
|View full text |Cite
|
Sign up to set email alerts
|

Adlay Seed (Coix lacryma-jobi L. var. Ma-yuen Stapf.) Ethanolic Extract Fractions and Subfractions Induce Cell Cycle Arrest and Apoptosis in Human Breast and Cervical Cancer Cell Lines

Abstract: The antitumor effects of Coix lacryma-jobi L. var. ma-yuen Stapf. (adlay seed) ethanolic extract have been increasingly shown. This study aimed to investigate the beneficial effects of both the fractions and subfractions of adlay seed ethanolic extract on the human breast (MCF-7) and cervical (HeLa) cancer cell lines, as well as exploring their possible mechanisms of action. The ethanolic extracts were obtained from different parts of adlay seed, including AHE (adlay hull extract), ATE (adlay testa extract), A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…An in-vitro study demonstrated that CSO upregulates the PTEN protein while inhibiting the expression of p-AKT and p-PI3K proteins, thereby inducing apoptosis in human pancreatic cancer cells through the PTEN/PI3K/AKT signaling pathway ( Yang et al, 2022a ). Additionally, Coicis semen has been found to inhibit proliferation and promote the apoptosis of various cancer cell types, including cancer cells of the lung ( Chang et al, 2003 ), colon ( Lee et al, 2008 ), hepatic ( Qu et al, 2016 ), mouth ( Manosroi et al, 2019 ), breast ( Fang et al, 2020 ; Chiang et al, 2022 ), uterine ( Huang et al, 2021 ), cervical ( Chen et al, 2018 ; Guo et al, 2019 ; Chiang et al, 2022 ), and pancreatic ( Yang et al, 2022a ). While not directly related to cardiovascular health, this could contribute to overall health and wellbeing ( Zeng et al, 2022 ).…”
Section: The Potential Impact Of Yyfz On Mitochondria-er Interactionsmentioning
confidence: 99%
“…An in-vitro study demonstrated that CSO upregulates the PTEN protein while inhibiting the expression of p-AKT and p-PI3K proteins, thereby inducing apoptosis in human pancreatic cancer cells through the PTEN/PI3K/AKT signaling pathway ( Yang et al, 2022a ). Additionally, Coicis semen has been found to inhibit proliferation and promote the apoptosis of various cancer cell types, including cancer cells of the lung ( Chang et al, 2003 ), colon ( Lee et al, 2008 ), hepatic ( Qu et al, 2016 ), mouth ( Manosroi et al, 2019 ), breast ( Fang et al, 2020 ; Chiang et al, 2022 ), uterine ( Huang et al, 2021 ), cervical ( Chen et al, 2018 ; Guo et al, 2019 ; Chiang et al, 2022 ), and pancreatic ( Yang et al, 2022a ). While not directly related to cardiovascular health, this could contribute to overall health and wellbeing ( Zeng et al, 2022 ).…”
Section: The Potential Impact Of Yyfz On Mitochondria-er Interactionsmentioning
confidence: 99%
“…Tumor samples (about 0.1 g) were homogenized with lysis buffer containing a protease inhibitor (Roche, Basel, Switzerland) and a phosphatase inhibitor (Roche) using TissueLyser II (Qiagen, Chatsworth, CA, USA) and centrifuged at 12,000× g for 30 min at 4 • C. A BCA kit (T-Pro Biotechnology, New Taipei City, Taiwan) was used to measure the tissue and serum protein concentration. We used 10-15% SDS-polyacrylamide gel electrophoresis (PAGE) for protein separation and then transferred the samples onto Immobilon-P polyvinylidene fluoride (PVDF) membranes (0.22 µm) for 125 min at 95 V. Then, we used blocking buffer (5% BSA) for 1 h at room temperature and incubated the samples with primary antibodies against NAMPT (Proteintech, Rehovot, Israel), NANOG (Proteintech), OCT4 (Proteintech), SOX2 (Proteintech), SIRT1 (Cell signaling, Boston, MA, USA), VEGF (Santa Cruz Biotechnology, Santa Cruz, CA, USA), and glyceraldehyde-3-phosphate dehydrogenase (GAPDH) (Proteintech, Rehovot, Israel) overnight at 4 • C. After washing 3 times, the samples were incubated with anti-rabbit/mouse IgG coupled with alkaline phosphatase (1: 10,000) for 2 h. We used an ECL chemiluminescent kit to visualize the antibody-antigen interaction and detected the signal with an eBlot Touch Imager (eBlot Photoelectric Technology, Shanghai, China) [20]. The relative intensity was measured using ImageJ software (NIH, Bethesda, MD, USA).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…and Mashinin (Cannabis Fructus). Some studies have analyzed lowmolecular compounds or polysaccharides that can be extracted into a low-polarity solvent in Yokuinin and investigated their effects in vitro and in vivo [63][64][65][66][67][68][69]. However, Li et al extracted the components in Yokuinin using high-polarity solvents, namely, 0.5 M sodium chloride aqueous, 70% ethanol aqueous, and 12.5 mM sodium borate buffer [18]; these four solvents contained albumin, globulin, prolamin, and glutelin, and their target was glutelin.…”
Section: Proteins In Crude Drugsmentioning
confidence: 99%